2005
DOI: 10.1136/jnnp.2005.062539
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance brain imaging in patients with acute stroke: feasibility and patient related difficulties

Abstract: Objectives: To assess organisational and patient specific limitations and safety of magnetic resonance imaging (MRI) as the first line investigation for hospital admitted stroke patients. Methods: Consecutive patients admitted with acute stroke were assessed and an attempt was made to perform MRI in all patients. Oxygen saturation and interventions required during scanning were recorded. Results: Among 136 patients recruited over 34 weeks, 85 (62%) underwent MRI. The patients' medical instability (15 of the 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 11 publications
0
63
0
4
Order By: Relevance
“…Feasibility of MRI may be limited in these frequently unstable patients. 23 Assessment of early ischemic changes on NCCT did not predict recanalization or functional outcome in patients with BAO in previous studies. 17,19 Similarly to anterior circulation stroke, CTASI improved the detection of ischemia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility of MRI may be limited in these frequently unstable patients. 23 Assessment of early ischemic changes on NCCT did not predict recanalization or functional outcome in patients with BAO in previous studies. 17,19 Similarly to anterior circulation stroke, CTASI improved the detection of ischemia in our study.…”
Section: Discussionmentioning
confidence: 99%
“…MR imaging also has limited availability "after hours." 20 Moreover, the recent MR Rescue Trial showed that the tool may not help in selecting patients for IAT. 21 NCCT ASPECTS has moderate interrater reliability, even among experts.…”
Section: Discussionmentioning
confidence: 99%
“…Collateral status by use of the rLMC score (0 -20) was trichotomized into 3 groups: good (17)(18)(19)(20), intermediate (11)(12)(13)(14)(15)(16), and poor (0 -10), according to previously published literature. 3 Differences between these 3 groups were assessed by means of the Fisher exact test for proportions, 1-way ANOVA for parametric data, and a rank sum test for nonparametric data.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…As a certain limitation, it should be mentioned that availability and feasibility of MRI is limited in acute stroke patients (Table 2) [8]. Some stroke patients cannot tolerate MRI or cooperate, poorly leading to movement artifacts.…”
Section: Magnetic Resonance Angiographymentioning
confidence: 99%